Advanced Inorganic Nitride Nanomaterials for Renewable Energy: A Mini Review of Synthesis Methods - Ma, Yin; Xiong, Lijun; Lu, Yao; Zhu, Wenqiang; Zhao, Haihong; Yang, Yahui; Mao, Liqiu; Yang, Lishan (Frontiers in Chemistry, 2021)
Inorganic nitride nanomaterials have attracted widespread attention for applications in renewable energy due to novel electrochemical activities and high chemical stabilities. For different renewable energy applications, there are many possibilities and uncertainties about the optimal nitride phases and nanostructures, which further promotes the exploration of controllable preparation of nitride nanomaterials. Moreover, unlike conventional nitrides with bulk or ceramic structures, the synthesis of nitride nanomaterials needs more accurate control to guarantee the target nanostructure along with the phase purity, which make the whole synthesis still a challenge to achieve. In this mini review, we mainly summarize the synthesis methods for inorganic nitride nanomaterials, including chemistry vapor deposition, self-propagation high-temperature synthesis, solid state metathesis reactions, solvothermal synthesis, etc. From the perspective of nanostructure, several novel nitrides, with nanostructures like nanoporous, two-dimensional, defects, ternary structures, and quantum dots, are showing unique properties and getting extensive attentions, recently. Prospects of future research in design and synthesis of functional inorganic nitrides are also discussed.